Bending of rectangular plates with large deflections - Levy, Samuel (Report (United States. National Advisory Committee for Aeronautics), 1942)
The solution of Von Karman's fundamental equations for large deflections of plates is presented for the case of a simply supported rectangular plate under combined edge compression and lateral loading. Numerical solutions are given for square plates and for rectangular plates with a width-span ratio of 3:1. --